Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil - Vianna, Rogério T.; Boeger, Walter A. (Zootaxa, 2019)
Two new species of Gyrodactylus are described from the body surface of two catfish species from southern Brazilian rivers. Gyrodactylus anaspidus n. sp. is described from the armored-catfish, Pareiorhaphis parmula (Loricariidae) and Gyrodactylus polyadenus n. sp. is described from the cascarudo, Callichthys callichthys (Callichthyidae). The new species differ from previously described neotropical species of Gyrodactylus by the relative morphology of their haptoral hard structures and male copulatory organ (MCO). Gyrodactylus anaspidus n. sp. has a superficial bar without a shield and an MCO with one row of spinelets (9–11 spinelets). Gyrodactylus polyadenus n. sp. presents a shield associated to a superficial bar, a deep bar with narrow extremities connected to the anchors, a subrectangular hooklet with a short point, and an MCO with one row of six spinelets. We also report that G. anaspidus n. sp. co-occurs with oviparous species of Gyrodactylidae on their respective loricariid hosts.